Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

On page 20 of "On the Random Character of Fundamental Constant Expansions", Bailey and Crandall gave the rather unusual sum,

$$u_2 = \sum_{n=0}^\infty \frac{1}{5^{5n}}\left(\frac{5}{5n+2}+\frac{1}{5n+3}\right) = \frac{5^2}{2}\ln\left(\frac{781}{256}\left(\frac{57-5\sqrt{5}}{57+5\sqrt{5}} \right)^\sqrt{5} \right) = 2.833601\dots$$

I found its counterpart,

$$u_1 = \sum_{n=0}^\infty \frac{1}{5^{5n}}\left(\frac{5^3}{5n+1}+\frac{1}{5n+4}\right) = \frac{5^3}{2}\ln\left(\frac{781}{256}\left(\frac{57+5\sqrt{5}}{57-5\sqrt{5}} \right)^\sqrt{5} \right) = 125.256703\dots$$

Note that $(57+5\sqrt{5})(57-5\sqrt{5}) = 4(781) = 5^5-1$. This can be generalized though. The case $p=7$ is straightforward, but $p=11$ is a bit tricky. Let,

$$\begin{aligned} v_1 &= \sum_{n=0}^\infty \frac{1}{11^{11n}}\left(\frac{11^9}{11n+1}+\frac{1}{11n+10}\right)\\ v_2 &= \sum_{n=0}^\infty \frac{1}{11^{11n}}\left(\frac{11^7}{11n+2}+\frac{1}{11n+9}\right)\\ v_3 &= \sum_{n=0}^\infty \frac{1}{11^{11n}}\left(\frac{11^5}{11n+3}+\frac{1}{11n+8}\right)\\ v_4 &= \sum_{n=0}^\infty \frac{1}{11^{11n}}\left(\frac{11^3}{11n+4}+\frac{1}{11n+7}\right)\\ v_5 &= \sum_{n=0}^\infty \frac{1}{11^{11n}}\left(\frac{11}{11n+5}+\frac{1}{11n+6}\right) \end{aligned}$$

and define,

$$c_k = -2\cos(2k\,\pi/11)$$

$$d = 11^2+1 = 122$$


$$\begin{aligned} v_1 &= 11^9 \ln\Big((11c_1+d)^{c_1}\,(11c_2+d)^{c_2}\,(11c_3+d)^{c_3}\,(11c_4+d)^{c_4}\,(11c_5+d)^{c_5}\,/10^2 \Big)\\ v_2 &= 11^8 \ln\Big((11c_1+d)^{c_2}\,(11c_2+d)^{c_4}\,(11c_3+d)^{c_5}\,(11c_4+d)^{c_3}\,(11c_5+d)^{c_1}\,/10^2 \Big) \\ v_3 &= 11^7 \ln\Big((11c_1+d)^{c_3}\,(11c_2+d)^{c_5}\,(11c_3+d)^{c_2}\,(11c_4+d)^{c_1}\,(11c_5+d)^{c_4}\,/10^2 \Big) \\ v_4 &= 11^6 \ln\Big((11c_1+d)^{c_4}\,(11c_2+d)^{c_3}\,(11c_3+d)^{c_1}\,(11c_4+d)^{c_5}\,(11c_5+d)^{c_2}\,/10^2 \Big) \\ v_5 &= 11^5 \ln\Big((11c_1+d)^{c_5}\,(11c_2+d)^{c_1}\,(11c_3+d)^{c_4}\,(11c_4+d)^{c_2}\,(11c_5+d)^{c_3}\,/10^2 \Big) \\ \end{aligned}$$

For clarity, the exponent $c_k$ have subscripts,

$$\begin{aligned} u_1 &= 1,2,3,4,5\\ u_2 &= 2,4,5,3,1\\ u_3 &= 3,5,2,1,4\\ u_4 &= 4,3,1,5,2\\ u_5 &= 5,1,4,2,3\\ \end{aligned}$$

Question: What is the formula for the sequence of exponent subscripts? (I noticed it is a Latin square, but how do you generate it?)

P.S. The case $p=13$ is analogous, and uses $d_{13} = 13^2+1 = 170$.

share|cite|improve this question
I was going to email Richard Crandall (the co-author of the paper cited) but found out from wikipedia that he died Dec 2012. :( – Tito Piezas III Sep 2 '13 at 1:40
up vote 2 down vote accepted

This is a late answer, but I hope it helps. In page 20 of the link, there's a formula $$\sum_{n=0}^\infty\frac1{b^n(dn+c)}=-\frac1db^{c/d}\sum_{a=0}^{d-1}e^{-2\pi iac/d}\log\left(1-\frac{e^{2\pi ia/d}}{b^{1/d}}\right)$$which can be proved by the talor expansion of $-\log(1-x)$. From this we have \begin{align}v_k&=\sum_{n=0}^\infty\frac{1}{p^{pn}}\left(\frac{p^{p-2k}}{pn+k}+\frac{1}{pn+p-k}\right)\\&=-p^{p-k-1}\sum_{a=0}^{p-1}(e^{-2\pi iak/p}+e^{2\pi iak/p})\log\left(1-\frac{e^{e\pi ia/p}}{p}\right)\\&=-p^{p-k-1}\sum_{a=0}^{p-1}\cos\frac{2\pi ka}{p}\log\left(p^2+1-2p\cos\frac{2\pi a}{p}\right)\\&=-p^{p-k-1}\left(\sum_{a=1}^{(p-1)/2}2\cos\frac{2\pi ka}{p}\log\left(p^2+1-2p\cos\frac{2\pi a}{p}\right)+\log(p-1)^2\right)\end{align} Let $c_k=-2\cos(2k\pi/p)$, $d=p^2+1$. Then the above can be expressed as $$v_k=p^{p-k-1}\log\left(\frac{1}{(p-1)^2}\prod_{a=1}^{(p-1)/2}(pc_a+d)^{c_{ka}}\right)$$ So the subscripts are all $ka$. Let $p=11$. Then $$v_1=1,2,3,4,5\\v_2=2,4,6,8,10\\v_3=3,6,9,12,15\\v_4=4,8,12,16,20\\v_5=5,10,15,20,25$$ Notice that $c_k=c_{p-k}=c_{p+k}$. The above can be transformed as $$v_1=1,2,3,4,5\\v_2=2,4,5,3,1\\v_3=3,5,2,1,4\\v_4=4,3,1,5,2\\v_5=5,1,4,2,3$$The fact that they form a Latin square follows from the fact that the $ka$ s are all different by modulo $p$.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.